Occurrence and antibiotics resistance signatures of Burkholderia Pseudomallei isolated from selected hospital final effluents in Akoko metropolis within Ondo State Nigeria - Ayodeji, Charles Osunla; Akinmolayemi, Thomas Akinmolayemi; Oluwatayo, A Makinde; Oluwatayo, E Abioye; Olotu, Emmanuel Juwon; Ikuesan, Felix Adeleke (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study investigated the occurrence of Burkholderia pseudomallei in the final effluent of some hospitals in Akoko metropolis. Burkholderia pseudomallei are the causative agent for melioidosis, a disease which affects both humans and animals. A total number of 155 presumptive Burkholderia species were recovered from thirty six different samples over a period of three months from effluent of three selected hospitals using conventional isolation techniques. A preliminary test was carried out on all the isolates and they were found to be oxidase positive. 67% of the recovered isolates were confirmed to be Burkholderia pseudomallei using Microbact™ 24E Identification kit. Antimicrobial susceptibility test carried out on the confirmed Burkholderia pseudomallei revealed that most isolates were susceptible to cefotaxime and ofloxacin but exhibited resistance against tetracycline and meropenem. The persistence of Burkholderia pseudomallei in the hospital environment throughout the sampling regime requires intervention strategies to eradicate the prevalence of this notable pathogen in all possible reservoirs within the hospital environment. Besides, the emergence of resistance particularly to tetracycline and carbapenems has serious clinical implications. Furthermore, surveillance of Burkholderia species with its antibiogram profiles in clinical environments and adequate treatment of hospital effluents before disposal is very important to avert potential outbreak of melioidosis because the main reservoir for B. pseudomallei is contaminated environments.